Emergency obstetric patients in developing countries and prevalence of HIV infection (2009)
The availability of VCT for HIV for booked antenatal patients offers a unique opportunity for best obstetrics practice but not for patients presenting with emergencies and unknown HIV status. Health workers who attend to such patients are at higher risk of acquiring HIV infections. Between 1st March 2005 and 30th September 2007, unbooked emergency obstetric patients in the labour ward of a teaching hospital who consented were tested using double rapid immunodiagnostic technique and confirmed by Western Blot. HIV positive patients were post-test counselled and offered single dose nevirapine tablet (200 mg) in labour with syrup given to the baby at birth at 2 mg/kg followed by syrup zidovudine for 6 weeks. The results showed that 275 (89.0%) of the 309 women pre-test counselled agreed to testing. The mean age of clients was 27.7 years (± 4.4 SD). The mean gestational age at presentation was 36.4 weeks (± 4.2 weeks). Primigravidae constituted 37.5% of the patients. Twenty-one (7.6%) of these consenting patients were HIV positive. In conclusion, the HIV prevalence of 7.6% among these unbooked obstetric patients is higher than the 4.7% among our booked antenatal patients and National prevalence of 4.4%. This poses substantial risk of transmission of HIV to attending health workers considering the readiness with which needle prick accident can occur in emergency situations.